Acute Renal Failure Associated with Combined Gentamicin and Cephalothin Therapy. Issue 5863 (19th May 1973) - Fillastre, J. P.; Laumonier, R.; Humbert, G.; Dubois, D.; Metayer, J.; Delpech, A.; Leroy, J.; Robert, M.
Abstract : Three patients with normal renal function developed acute renal failure between the ninth and twenty-seventh days of combined gentamicin and cephalothin therapy. The dose of gentamicin (4-6 mg/kg/day) was in the normal range, but that of cephalothin (180 mg/kg/day) was abnormally high. The nephropathy was of the tubular-interstitial type and the clinical picture similar to that seen in acute drug-induced nephropathies. Frusemide was given only after the onset of renal failure. In these three patients the high intravenous doses of cephalothin combined with gentamicin were probably nephrotoxic.